Effects of polysaccharides from Gastrodia elata on the immunomodulatory activity and gut microbiota regulation in cyclophosphamide‐treated mice. (24th February 2023) - Li, Na; Wang, Dan; Wen, Xingjian; Chu, Rui; Fan, Jiuyu; Chen, Yilong; Luo, Yanfeng
Abstract: BACKGROUND: Cyclophosphamide (CTX) is a widely used chemotherapeutic agent for the treatment of malignant tumors and autoimmune diseases. However, it can cause immunosuppression and damage the intestinal mucosa. The development of new agents to counteract these side effects is becoming increasingly important. Previous studies have shown that the polysaccharides from Gastrodia elata (GEPs) have strong immune‐enhancing effects; however, their functions regarding the intestines and the underlying mechanism are still unclear. In this study, the effects of GEPs on immunomodulatory activity, intestinal barrier function, and gut microbiota regulation were investigated in a mouse model of CTX‐induced immunosuppression. RESULTS: Gastrodia elata polysaccharides attenuated the CTX‐induced decrease in organ indices of the thymus and spleen, and promoted the secretion of immune‐related cytokines and immunoglobulins in the serum. They also improved the intestinal pathology and restored the intestinal barrier function by elevating the expression of intestinal tight junction proteins, occludin and ZO‐1. Moreover, GEPs restored the composition and abundance of the gut microbiota and increased the short‐chain fatty acid (SCFA) content in the colon. The abundance of SCFA‐producing bacteria (Muribaculaceae, Prevotellaceae, and Bacteroidaceae) also increased. CONCLUSIONS: Gastrodia elata polysaccharides can effectively alleviate immunosuppression and regulate the intestinal barrier integrity and the structure of gut microbiota in CTX‐treated mice. They may be used as ingredients to develop functional foods for intestinal health. © 2023 Society of Chemical Industry.